YELLOW CORN BISCUITS FOR EARLY CHILDHOOD: HIGH ENERGY AND BETA-CAROTENE (Jurnal Bahan Alam Terbarukan, 2018)
Snacks which are most widely consumed by early childhood are biscuits. The conventional raw ingredients of biscuits are varied with yellow corn starch, which contains beta-carotene. The composition of yellow corn biscuit consists of 50% yellow corn starch, 40% wheat flour, and 10% cornstarch, and butter. The use of butter was varied in 25%, 30%, and 35%. An analysis was conducted on its energy content, protein, fat, and beta-carotene, as well as acceptance. The results of the study showed nutrient content was not entirely different from the use of margarine 25% and 35%, the energy was 441-468 kcal, protein was 6.4 to 7.3%, fat was 18.3 to 21.7%, and beta-carotene 2,721 -4,134 mg. The energy density of corn biscuits was 3.5 - 3.9 g / 1000 kJ. Yellow corn biscuits were considered as high-energy biscuits ( 400 kcal). The organoleptic test of the biscuits in early childhood conducted on all indicators (color, aroma corn, fragrant aroma, and crispness, sweet and savory taste) showed that the biscuits were categorized as likable. The use of different percentage of margarine is not significant concerning the acceptability of biscuits, except for the aspect of the fragrance and sweetness between the use of margarine 30% to 35%. Industrial-scale production is necessary for the dissemination of the consumption of yellow corn biscuits with margarine 35%, in particular for the early childhood